2009
DOI: 10.22605/rrh1266
|View full text |Cite
|
Sign up to set email alerts
|

Developing strategies to enhance health services research capacity in a predominantly rural Canadian health authority

Abstract: Context: This article outlines the planning, implementation and preliminary evaluation of a research capacity building (RCB) initiative within a predominantly rural Canadian health authority, Interior Health (IH), including initiative characteristics and key activities designed to initiate and enhance health services research capacity within the organization. Interior Health is one of 5 geographic health authorities in British Columbia. Over half of the population IH serves is considered to be rural/remote (ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Research capacity-building opportunities are critical to building and sustaining rural health research [ 4 , 44 46 ]. In our study we identified an increase in rural research capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Research capacity-building opportunities are critical to building and sustaining rural health research [ 4 , 44 46 ]. In our study we identified an increase in rural research capacity.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate rural research and practice (a) there must be an integration of rural experiences in nursing education, (b) nursing students must be recruited from rural settings, and (c) nursing education must be delivered from rural settings (Bushy & leipert, 2005). Strategies to integrate research and eBP projects require course assignments, collaboration with clinical partners on research applicable to clinical practice, and provision of networking and educational opportunities-academic/clinical partnerships (Miller et al, 2009). Dr. Winters and her faculty colleagues have worked to increase collaboration efforts in western Montana.…”
Section: Phase 3 (2007-2012)mentioning
confidence: 99%